The Influence of Financial Performance on Profit Growth with Dividend Policy as a Moderating Variable in BUMN Banking Listed on the IDX for the 2019-2023 Period - Setiawan, Yayan; Megawati, Liya (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
The aim of this research is to obtain empirical evidence regarding the influence of company financial performance which is proportional to the current ratio, total assets turnover and return on assets. This research also tests dividend policy as a moderating variable which is proportional to the dividend payout ratio. The following study uses descriptive descriptive research methods with a quantitative approach.  Secondary data contained in this study includes financial data from BBRI, BBNI, BMRI and BBTN for the 2019-2023 period. Data processing was carried out using the SPSS version 25 program. The results of this research show that simultaneously all variables in the research have an effect on financial growth. Individually, the variables CR and TATO have no influence, on the other hand, ROA has a significant influence. The DPR variable is able to moderate and strengthen the CR variable, on the other hand the DPR variable is not able to moderate the TATO and ROA variables on profit growth.